Applying Lean Principles to Reduce Curriculum Process Time by Using ECRS Technique Case Study: Faculty of Engineering and Technology, Rajamangala University of Technology Isan - Nachaisit, Prin; Siripaiboonsub, Phatthawit; Nutkhum, Wannisa; Nithikarnjanatharn, Jittiwat; Phontang, Bhoomboon; Phongphattarawut, Worapong (Journal of Advanced Development in Engineering and Science, 2024)
This study aims to apply Lean principles to reduce the time required for curriculum development at the Faculty of Engineering and Technology, Rajamangala University of Technology Isan. The time taken for activities related to the development of five curricula was gathered through interviews, document collection, surveys, and data collection forms, revealing a total of 39 activities. The average time for curriculum development was found to be 1 year and 3 months. The study then analyzed delays in the curriculum development process by examining the 7 wastes, employing cause and effect diagrams, and conducting a Failure Mode and Effect Analysis (FMEA) to determine the Risk Priority Number (RPN) and prioritize issues. Further problem analysis using the Why-Why Analysis technique led to the identification of four solutions to reduce process time: Using a Kanban system to signal delays, implementing an online information system for data delivery, applying the ECRS (Eliminate, Combine, Rearrange, Simplify) method, providing training for staff. New activities were simulated using the ECRS principles to improve processes by focusing on eliminating non-value-added activities. A comparison between some activities in the old and new processes was conducted using data collection forms. The curriculum development time was reduced from 456.69 days to 296.09 days, a decrease of 35.16%. Additionally, the risk priority number in the FMEA analysis decreased from 1310 to 606, a reduction of 53.74%.